MASALAH-MASAIAH DAN SOLUSI BUDIDAYA PADI SAWAH - Arman Effendi A R (Universitas Riau, 2010)
The main factor causingtownational rke production is the km productivity ofricecrops in Indonesiathat is less than 4.66 ton/ha in mineral soil. Efforts to expand rice cultivation is very limited, because thefertile hnd has no longer available while marginal land still has obstacles (o develop cultivation of paddies.Some of tiie proUenis encountered in wedand development in Indonesiatekm pU so3 which shouM be improvedand limited soil nutrient availability, increase in the solubiiity of Fe and Fe toxklty problem, lack of potassiumdement because ail crops were tramiported oat; goieral fertilizerrecommendationis applied for each tocatktn/diirereot land; lack of research on h>cat)on-specifk fertilizer recsommendatiott; much water is needed (o moistsoil; and land productK'ity is still low. Optimal management of wetland win affect some aspects such as: soilnutrient status of fidds needs to be tested as a baus for determining fertilizer recommendation: microbialfertilizer technology to improve the efTiciency of fertilization, irrigation and leaching processes on wetlandmanagement can change tbe chemical properties of soil, crop ntaiugement development in traditional Indonesianrice cultivation should be done with SRI, because it can increase the productivity ofriceand of sustainableagriculture.